Assessment of Climate Variability for Coconut and Other Crops: A Statistical Approach - Peiris, T. S. G.; Kularatne, J. D. J. S. (International Coconut Community Journal, 2008)
Public opinion in Sri Lanka has been seriously concerned about the possible impact of climate change on different sectors, and in particular for the agricultural sector. Annual and weekly climate data were analyzed to provide useful information to farmers, planners and scientists to assess the suitability of different types of crops. The statistical methodology of the analysis is illustrated using daily rainfall and air temperature from 1951 to 2001 for Hambantota, a major coconut growing district in Sri Lanka. The increase in maximum air temperature and decrease in the amount of rainfall per effective rainy day (> 5mm) are the significant features of the climate variability in the Hambantota area. The warming rate for maximum air temperature was significantly higher (p<0.005) than that for minimum, mean and diurnal temperature, irrespective of time scales. The annual rate of increase of maximum temperature after 1995 is 0.0260C. The intensity of rainfall per effective rainy day (> 5mm) decreased significantly (p<0.005). Distribution of weekly rainfall during January to September is uncertain. The probability of weekly rainfall greater than 20 mm does not exceed 50% in any week during this period. Long-term weekly rainfall was greater than 30 mm only during mid October to early December, but the probability of weekly rainfall greater than 30 mm exceeds 50% only during the first three weeks of November. The probability of occurrence of dry spells of duration greater than 60 days in a year is around 70%, but the time of occurrence of such dry spell is not consistent among years. These findings suggest that the expected future climate would not be suitable for coconut cultivation, if growers do not apply the recommended practices to face long dry spells. Also the increasing temperature could impact to dominate plant pest during dry periods.